Investigation of the Effect of Different Screening_x000D_ Methods on Print Quality in Digital Printing System - ÖZOMAY, ZAFER (My University, 2021)
Digital printing is the process of printing the designs and photos prepared in computer environment with advanced printingtechnologies on different materials in a high quality and fast way. The digital printing system, which is increasing its effectivenesstoday, has taken great steps with technology since the first years of its existence and has started to have a voice in the sector for thelast ten years. The digital printing, which is an alternative to the offset printing system in making design a product, exhibitssignificant improvements in terms of production efficiency, cost and quality. Offset has become competitive with flexo printingwith the developing color efficiency in digital printing machines. High quality and different applications can be made with digitalprinting machines. In order to achieve this (screening) process, it is necessary to know the boundaries of the color universe that canbe seen or produced by the devices and machines used in the system. In this study, the difference between colors and colorconsistency and basic measurements such as color values, dot gain were evaluated by changing the selection of screen methodsused in digital printing. The differences caused by the screening structure variable have been shown with graphics and tables, thensuggestions have been made. It has been determined that the change in the screening structures in digital printing creates differencesin dot swelling, density and color.

Dijital baskı, ileri baskı teknolojileri ile bilgisayar ortamında hazırlanan tasarım ve fotoğrafların farklı malzemeler üzerine kaliteli_x000D_ ve hızlı bir şekilde basılması işlemidir. Günümüzde etkinliğini artıran dijital baskı sistemi, kurulduğu ilk yıllardan itibaren teknoloji_x000D_ ile büyük adımlar atmış ve son on yıldır sektörde söz sahibi olmaya başlamıştır. Tasarımı ürün haline getirmede ofset baskı_x000D_ sistemine alternatif olan dijital baskı, üretim verimliliği, maliyet ve kalite açısından önemli gelişmeler sergiliyor. Ofset, dijital baskı_x000D_ makinelerinde gelişen renk verimliliği ile flekso baskı ile rekabete girmiştir. Dijital baskı makineleri ile kaliteli ve farklı_x000D_ uygulamalar yapılabilmektedir. Bu (perdeleme) işleminin gerçekleştirilebilmesi için sistemde kullanılan cihaz ve makinelerin_x000D_ görülebildiği veya üretebildiği renk evreninin sınırlarının bilinmesi gerekmektedir. Bu çalışmada, dijital baskıda kullanılan ekran_x000D_ yöntemlerinin seçimi değiştirilerek renkler ile renk tutarlılığı arasındaki fark ve renk değerleri, nokta kazancı gibi temel ölçümler_x000D_ değerlendirilmiştir. Tarama yapısı değişkeninin neden olduğu farklılıklar grafik ve tablolarla gösterilmiş ve önerilerde_x000D_ bulunulmuştur. Dijital baskıda eleme yapılarındaki değişimin nokta şişmesi, yoğunluk ve renkte farklılıklar yarattığı tespit_x000D_ edilmiştir._x000D_
Dijital Baskı Sisteminde Farklı Tramlama Yöntemlerinin Baskı Kalitesine Etkisinin İncelenmesi